Draft genome sequences of extended-spectrum β-lactamase-producing escherichia coli strains isolated from patients in Lebanon - Tokajian, Sima (2014)
We present the draft genome sequences of nine extended-spectrum β-lactamase (ESBL)-producing Escherichia coli strains isolated from stool samples collected from patients admitted for gastrointestinal and urological procedures/surgeries. An average of 3,889,300 paired-end reads per sample were generated, which assembled in 77 to 157 contigs.